Kriminalisasi Poligam Di Negara Muslim Pada Era Kontemporer - M. Burhanuddin Ubaidillah (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
Polygamy can be likened to a double-edged sword. On one hand, polygamy is rejected with various normative arguments, citing the psychological well-being of women, both mentally and in terms of fairness. Western writers often accuse polygamy as evidence of Islamic teachings, particularly in the field of marriage, marginalizing women. On the other hand, polygamy is advocated because it has a strong normative basis and is seen as one alternative to address the phenomena of infidelity and prostitution. Polygamy practitioners find support from religious law aspects that permit polygamous practices up to the fourth wife if the husband is capable of providing and treating his wives justly. Supporters of polygamy consider it unnatural for the state to ban polygamy, let alone threaten illegal polygamists with criminal sanctions categorized as minor offenses (rechtsdeliktern). This article focuses on studying the issues of criminalizing polygamy and its practices in Muslim countries using a normative law research approach. The objective of this article is to contribute to the understanding of criminal penalties for polygamy practitioners in Muslim countries.